Understanding vigilance and its decrement: theoretical, contextual, and neural insights - Hemmerich, Klara; Luna, Fernando G.; Martín-Arévalo, Elisa; Lupiáñez, Juan (Frontiers in Cognition, 2025)
The vigilance decrement refers to the gradual decline in the ability to monitor the environment and detect rare but critical stimuli over time. This phenomenon occurs in many everyday situations and work environments and may be exacerbated by brain damage or developmental disorders. However, despite its seeming omnipresence, the exact meaning of “vigilance” and vigilance decrement is often unclear, with the term “vigilance” frequently used interchangeably with related concepts such as arousal, alertness, or sustained attention. This narrative review seeks to clarify this conceptual overlap, offering a precise definition of vigilance, whilst separating it from these other phenomena. Furthermore, this narrative review also provides a detailed account of some of the factors that modulate vigilance performance, as well as an overview of current theories that explain its frequent and progressive decrement over time. Lastly, it highlights the most relevant structural and electrophysiological correlates of its proper functioning. By integrating these insights, a more refined understanding of vigilance and its decrement may emerge, helping to unify future research findings and facilitate the development of interventions to mitigate its effects.